An uncommon complication of a common clinical scenario: exploring reexpansion pulmonary edema with a case report and literature review - Jared W. Meeker; Amy L. Jaeger; William P. Tillis (Greater Baltimore Medical Center, 2016)
Reexpansion pulmonary edema (RPE) is a rare complication that can occur after rapid reinflation of the lung following thoracentesis of a pleural effusion or chest tube drainage of pneumothorax. The severity in clinical presentation can be widely varied from radiographic changes only to rapidly progressive respiratory failure requiring mechanical ventilation. The quick nature of onset and potential for serious decline in a previously stable patient makes it important to prepare, recognize, diagnose, and appropriately manage patients who develop RPE. The standard treatment for RPE consists of supportive care, and there are certain measures that may be taken to reduce the risk, including limiting the amount drained and avoiding excessive negative pleural pressure. Exactly how to prevent RPE remains unclear, however, and varying recommendations exist. This is a case report of RPE after thoracentesis for a pleural effusion and a brief review of literature to date, including potential preventative strategies.